Aspiring high in the Swiss VET-dominated education system : second generation young adults and their immigrant parents - Kamm, Chantal [Verfasser]; Gomensoro, Andrés [Verfasser]; Heers, Marieke [Verfasser]; Hupka-Brunner, Sandra [Verfasser] (My University, 2023)
"Often second generation young adults and their immigrant parents aspire high and towards general education despite a modest socioeconomic background. Little is known about the interrelation between educational aspirations and institutionally co-structured educational pathways. These interrelations are particularly important in an early tracking and a highly segregated education system like Switzerland, where – in contrast to many other countries – vocational education and training is highly valued and frequently attended. We evaluate how educational aspirations amongst young adults of the second generation and Swiss natives change as young people move through the education system – and thus through different educational contexts. We analyse how these changes interfere with group-specific reference systems, educational pathways and structure." (Author's abstract ; BIBB-Doku)
Keywords: I 2.2.1 Westeuropa; G 1.3.2 Bildungsverhalten und -verläufe; 370; Migrant; Migrationshintergrund; Schweiz; zweite Generation; Bildungsaspirationen; Bildungsverlauf